Prey stages preference of different stages of Typhlodromus bagdasarjani (Acari: Phytoseiidae) to Tetranychus urticae (Acari: Tetranychidae) on rose - Mona Moghadasi; Alireza Saboori; Hossein Allahyari; Azadeh Zahedi Golpayegani (Persian Journal of Acarology)
Tetranychus urticae Koch is one of the most injurious tetranychid mites on greenhouse roses. Typhlodromus bagdasarjani Wainstein & Arutunjan is a generalist indigenous phytoseiid mite with a wide distribution in Iran and frequently reported from plants infested by tetranychids. In this research, the preference of protonymph, deutonymph and adult of T. bagdasarjani on different stages of T. urticae was studied under laboratory conditions (25 ± 1°C, 75 ± 5% RH and 16L: 8D h. of photoperiod). The experiment was carried out on rose leaf square (blarodje variety). The preference index for each predator stage was calculated with Manly’s β index. Comparison of the mean preference index for protonymph (F = 135.61; df = 3, 84; P < 0.0001), deutonymph (F = 264.71; df = 3, 83; P < 0.0001) and female (F = 173.52; df = 4, 119; P < 0.0001) of the predator showed that all stages significantly preferred T. urticae eggs followed by prey larvae and protonymphs. Due to the our results can be suggested that T. urticae eggs are more profitable prey stage for T. bagdasarjani than other stages with regard to both nutritional benefit and handling time.